Comparison study of the effect of CeO2-based carrier materials on the total oxidation of CO, methane, and propane over RuO2. Issue 20 (15th September 2021) - Wang, Zheng; Khalid, Omeir; Wang, Wei; Wang, Yu; Weber, Tim; Spriewald Luciano, Alexander; Zhan, Wangcheng; Smarsly, Bernd M.; Over, Herbert
Abstract : While activity and kinetics of catalytic CO and propane combustion over RuO2 depends sensitively on the carrier material, methane combustion on RuO2 is hardly affected by the carrier. Abstract : The effect of the carrier material on the intrinsic activity of three catalytic total oxidation reactions, namely CO oxidation and methane and propane combustion, over highly dispersed RuO2 is studied. The carrier materials are systematically varied from ZrO2 to CeO2 using ultrathin CeO2 films on ZrO2 particles (CeO2 @ZrO2 ) as the linking carrier materials that were subjected to different calcination and redox treatments. CeO2 @ZrO2 is subjected to annealing to 900 °C, transforming the CeO2 layer into a mixed Ce x Zr1− x O2 layer, and finally, after reductive treatment with H2 at 950 °C and mild re-oxidation at 500 °C a kappa phase layer is formed on the ZrO2 core. The catalytic CO oxidation and the propane combustion reveal pronounced dependencies on the carrier material. The variation in propane combustion activity with the carrier material is correlated with the varying surface concentration of vacant surface Ce sites, while the activity in CO oxidation is correlated with the oxygen storage capacity (OSC). Quite in contrast, the intrinsic activity and the apparent activation energy in methane combustion are less affected by the carrier material than in the other two reactions. For comparison we chose rutile TiO2 as the carrier that is known to disperse RuO2 quite efficiently, revealing, however, by far the lowest activity in all total oxidation reactions studied, due likely to strong metal–support interaction (SMSI).